Axillary accessory breasts in a 13-year-old girl. - Mazzotta, F.; Genchi, V.; Zorlu, O. (European Journal of Pediatric Dermatology, 2023)
Accessory breasts, areolas and nipples can follow the non-regression of embryonic residues along the so-called milk-line that goes from the armpit to the pubis. When glandular residues are not associated with nipples and areolas, diagnostic problems arise: a careful history that highlights significant variations during the menstrual period and ultrasound allow a correct diagnosis. A case of bilateral axillary accessory breasts in a 13-year-old girl is described.